2020
DOI: 10.21608/jappmu.2020.118215
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spirulina platensis Supplementation in Growing Rabbit's Diet on Productive Performance and Economic Efficiency

Abstract: The current study carried out to assessment the effect of addition of low levels 0.3 and 0.6 g/kg diet of Spirulina platensis (SP) on the productive performance and economic efficiency parameters of growing Red Balady rabbits for 8 weeks. A total of 36 growing rabbits (6-week old) were randomly assigned into three dietary experimental treatments (12 rabbits of each), that was conducted from 6 to 14 weeks of age. The obtained results revealed that addition of SP to the diet of growing rabbits at level 0.6 g/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
2
2
0
Order By: Relevance
“…The findings of this study are also in line with the results of EL-Sabagh et al (2014), who reported that spirulina supplementation increased liveweights in fattening lambs from 47.0 to 55.3 kg and in growing pigs from 12.47 to 33.60 kg (Nedeva et al 2014). Also, in agreement with our results, Alazab et al (2020) found that adding SP to the diet of rabbits enhanced growth and performance and the FCR.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of this study are also in line with the results of EL-Sabagh et al (2014), who reported that spirulina supplementation increased liveweights in fattening lambs from 47.0 to 55.3 kg and in growing pigs from 12.47 to 33.60 kg (Nedeva et al 2014). Also, in agreement with our results, Alazab et al (2020) found that adding SP to the diet of rabbits enhanced growth and performance and the FCR.…”
Section: Discussionsupporting
confidence: 92%
“…upplementation of late pregnant ewes with Nannochloropsis induced a significant increased in WBCs, Hb, RBc count in the supplemented ewes and their newly born lambs as compared with the control group. The present study's findings were in line with those of (EL-Sabagh et al 2014) for fattening lambs and (Ghattas et al 2019) in calves, but they differed from those of (Alazab et al 2020) who discovered that all tested hematological parameters of growing rabbits treated with Spirulina platensis showed non-significant improvements when compared to the control group. Leukocytes play a vital role in nonspecific or innate immunity, and their numbers can be viewed as indicators of relatively low susceptibility to disease (Matanović et al 2007).…”
Section: Discussionsupporting
confidence: 88%
“…Several studies have demonstrated that adding algal biomass or extracts improves growth and nutrient use. In Arthrospira impacts regard, Alazab et al 20 found that adding Spirulina platensis (SP) to the diet of growing rabbits at a level of 0.6 g/kg diet resulted in considerably better growth performance parameters and enhanced feed conversion ratio in comparison to those provided the low level (0.3 g/kg diet) or those fed a basal diet. Moreover, Aladaileh et al 21 highlighted that exogenous supplementation of SP enhanced the growth traits of rabbits subjected to Pb.…”
Section: Discussionmentioning
confidence: 99%